Onward Migration and Multi-Sited Transnationalism Complex Trajectories, Practices and Ties - Ahrens, Jill; King, Russell (IMISCOE Research Series,, 2023)
This open access book brings novel perspectives to the scholarship on transnational migration. The book stresses the complexity of migration trajectories and proposes multi-sited field studies to capture this complexity. Its constituent chapters offer examples of onward migration spanning all major world regions. The contents exemplify a range of interdisciplinary approaches, including both qualitative and quantitative methodologies. The result is an impressive remapping and reconceptualisation of global migration and mobility, of interest to students and policy-makers alike.